Nurcholish Madjid's Multiperspective Neuroparaemiophenomenology of Love - Kao, Tzu-Jen; Anurogo, Dito; Rachman, Budhy Munawar; Ikrar, Taruna (Journal of Islamic Civilization, 2022)
Unification theory seeks to gain a comprehensive understanding of something. The goal of unification theory is to bring together multiviews on love. If “Love” is not understood from multiple perspectives, it will be difficult to understand and easy to misinterpret. This paper expresses Nurcholish Madjid's "Love" thoughts based on his works. Given the scope of the issue, Love will be examined through the lens of neuroparemiofenomenology, or the collaboration of neuroscience, paremiology, and phenomenology. The term "Love" was searched using "Nurcholish Madjid's Complete Works," edited by Dr. Budhy Munawar-Rachman. The neuroparemiopheno menological perspective is hoped to reveal the fundamental meaning of "love" in a comprehensive and complete manner. Teori unifikasi berusaha untuk memperoleh pemahaman yang komprehensif tentang sesuatu. Tujuan dari teori unifikasi adalah untuk menyatukan berbagai pandangan tentang cinta. Cinta akan sulit dipahami dan mudah disalahtafsirkan bila tidak dimengerti melalui multiperspektif. Tulisan ini mengungkapkan pemikiran "Cinta" ala Nurcholish Madjid berdasarkan karya-karyanya. Mengingat luasnya problematika, maka Cinta akan dibahas berdasarkan perspektif neuroparemiofenomenologi, yakni: kolaborasi antara neurosains, paremiologi, dan fenomenologi. Terminologi "Cinta" dicari berdasarkan "Karya Lengkap Nurcholish Madjid" dengan Dr. Budhy Munawar-Rachman selaku ketua penyunting. Diharapkan perspektif neuroparemiofenomenologi dapat mengungkapkan makna fundamental "cinta" secara komprehensif dan paripurna.